Efektifitas Terapi Caring Support Neobil terhadap Perubahan Kadar Bilirubin Serum Total Hyperbilirubinemia pada Neonatus Di Rumah Sakit Dustira Cimahi - An'nisaa Heriyanti; Restuning Widiasih; Murtiningsih (Poltekkes Kemenkes Kendari, 2020)
Less breast feeding and slow treatment of light therapy can strengthen the accumulation of bilirubin in the blood. The purpose of this research is to know the effectiveness of caring therapy NEOBIL to change the value of bilirubin levels of serum hyperbilirubinemia total physiological in neonatal in Dustira Hospital, Cimahi City. The research design uses a quasi-experiment with a non-equivalent control group design pre-test post-test. Samples were taken consecutive divided into intervention groups (29 respondents) and control groups (29 respondents) following the criteria of inclusion. The research instrument used is the action observation sheet and machine tool of TMS 24i & 50i. Data is analyzed using a t-test paired and independent t-test. Results showed average levels of total serum bilirubin after intervention in the intervention group (9.17) while the control group (11.23) between the two groups was a meaningful decline (P-value 0.002). Based on the results of Caring therapy Research support NEOBIL more effectively statistically help light therapy lowers the value of total serum bilirubin.